Desfaceti parantezele:
a)(2x-3y)(5x+7y-1)
Utilizator anonim:
(2x-3y)(5x+7y-1)=10x^2-15xy+14xy-21y^2-2x-3y=10x^2xy-2x-3y-21y^2
Răspunsuri la întrebare
Răspuns de
11
(2x-3y)(5x+7y-1) = 10x^2+14xy+2x-15xy-21y^2+3y=10x^2 -21y^2 +2x +3y - xy
Răspuns de
5
(2x-3y)(5x+7y-1)=10x²-15xy+14xy-21y²-2x-3y=10x²xy-2x-3y-21y²
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Limba română,
9 ani în urmă